Determination of Optimal Pulse Current for ArcWelding - Ščemeliovas, J. (Elektronika ir Elektrotechnika, 2009)
The manual and semi-automatic welding by pulse current (pulsing arc) is considered in the article. The advantages of welding by the pulsing arc are found out in comparison with welding by a constant arc. Using energetic calculation taking into account thermal balance at the electrode stub, optimal parameters of modulated current, such as frequency and duration of electrical pulses were established for different welding methods and regimes. By that stabilized heat, which needed for making melting drops, lower the level of metal splash and improve formation of the weld. Bibl. 12 (in English; summaries in English, Russian and Lithuanian).